When Earnings Management Becomes a Signal: Information Asymmetry, Corporate Governance, and Firm Value - Erna Hernawati; Husnah Nur Laela Ermaya; Poppy Sofia Koeswayo (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study examines how information asymmetry, financial distress, and earnings management are associated with firm value, and investigates the role of corporate governance in conditioning the market valuation of discretionary reporting behavior. The study adopts a quantitative explanatory research design using firm-level secondary data from non-financial publicly listed firms operating in manufacturing and manufacturing-related sectors in Indonesia. The final sample consists of 1,321 firm-year observations. The empirical analysis employs a path analysis approach with observed variables, enabling the simultaneous estimation of direct effects, indirect effects through earnings management, and moderating effects involving corporate governance. Model estimation is conducted using maximum likelihood techniques. The results indicate that information asymmetry and earnings management are negatively associated with firm value, while financial distress does not exhibit a significant direct effect. Earnings management does not mediate the relationships between information asymmetry or financial distress and firm value. However, corporate governance plays a significant moderating role by attenuating the negative association between earnings management and firm value. This finding suggests that the market evaluates discretionary reporting behavior conditionally, depending on governance quality. The study relies on accounting- and market-based proxies within an associative empirical framework, which limits causal interpretation. The findings nevertheless highlight the importance of incorporating governance-related conditional mechanisms when examining the economic consequences of financial reporting practices. This study contributes to the literature by positioning corporate governance as an interpretive mechanism that conditions the valuation consequences of earnings management rather than merely constraining managerial discretion. By integrating moderation and mediation structures within a unified empirical framework, the study offers a more nuanced understanding of how the market evaluates financial reporting behavior in an emerging economy context.